The solution of the equation is
and ![y=1](https://tex.z-dn.net/?f=y%3D1)
Explanation:
The equations are
and ![y=-2 x+7](https://tex.z-dn.net/?f=y%3D-2%20x%2B7)
First we shall solve the equation graphically.
The image of the graph is attached below.
This contains the solution to the system of equations.
The equations
and
are plotted on the graph.
The intersection of these two equations are the solutions of the system of equations.
Thus, the intersection of the two equations are
and ![y=1](https://tex.z-dn.net/?f=y%3D1)
Now, we shall solve the equation algebraically.
Let us solve the equation using substitution method.
Let us substitute
in
, we get,
![x-2=-2x+7](https://tex.z-dn.net/?f=x-2%3D-2x%2B7)
Adding both sides by 2x, we have,
![3x-2=7](https://tex.z-dn.net/?f=3x-2%3D7)
Adding both sides by 2, we get,
![3x=9](https://tex.z-dn.net/?f=3x%3D9)
Dividing both sides by 3,
![x=3](https://tex.z-dn.net/?f=x%3D3)
Thus, the value of x is 3.
Substituting
in
, we get,
![y=3-2\\y=1](https://tex.z-dn.net/?f=y%3D3-2%5C%5Cy%3D1)
Thus, the value of y is 1.
Hence, The solution of the equation is
and ![y=1](https://tex.z-dn.net/?f=y%3D1)